Simultaneous dual-color amplified spontaneous emissionand lasing from colloidal quantum well gain media intheir own layered waveguide and cavity - Isik, Ahmet Tarik (2023)
Micro/nanoscale semiconductor multicolor lasers offer great potential for enhanced-performance photonic circuits. Colloidal quantum wells (CQWs) are excellent candidates as active materials for these platforms owing to their superior properties including suppressed Auger recombination and large absorption cross-section. In this work, multicolor optical gain and lasing from the heterostructures of CQWs as the gain media in their own all-solution processed optical cavity are proposed and demonstrated for the first time. Here, using a simple waveguide slab consisting of the thin films of green-emitting CdSeS/Cd0.1Zn0.9S core/hot-injection-shell grown CQWs and red-emitting CdSe/CdS@CdZnS core/crown@shell CQWs, a transparent low refractive index colloidal spacing layer of silica nanoparticles (NPs) is devised that critically suppresses otherwise detrimental nonradiative energy transfer between the green and red-emitting CQWs. This multilayer configuration is key to enabling simultaneous amplified spontaneous emission behavior in two colors with low threshold levels. This layered architecture is further adapted to a whispering-gallery-mode cavity by fabricating a microdisk pattern directly out of these CQWs-NPs-CQWs colloids. The resulting device exhibits dual-color multimode lasing both at 569 and 648 nm at the same time. This unique multicolor lasing layered architecture holds great promise for on-chip photonic applications such as dual-color biological imaging.